2015
DOI: 10.3389/fpls.2015.00086
|View full text |Cite
|
Sign up to set email alerts
|

Exploring bacteria-induced growth and morphogenesis in the green macroalga order Ulvales (Chlorophyta)

Abstract: Green macroalgae, such as Ulvales, lose their typical morphology completely when grown under axenic conditions or in the absence of the appropriate microbiome. As a result, slow growing aberrant phenotypes or even callus-like morphotypes are observed in Ulvales. The cross-kingdom interactions between marine algae and microorganisms are hence not only restricted by the exchange of macronutrients, including vitamins and nutrients, but also by infochemicals such as bacterial morphogenetic compounds. The latter ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
115
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 129 publications
(130 citation statements)
references
References 113 publications
2
115
0
4
Order By: Relevance
“…However, P. yezoensis and B. fuscopurpurea have no OPDA (Mori, Matsuura and Mikami, unpublished), which is consistent with the lack of JA in these Bangiophyceae. Moreover, in P. patens, despite the absence of bioactive GA 1 and GA 4 , the precursors ent-kaurene and ent-kaurenoic acid and also their metabolites other than GAs regulate red light-dependent cellular differentiation and blue light-dependent negative phototropism (Hayashi et al 2010, Miyazaki et al 2014, 2015. However, little is known so far about the presence of these molecules in red seaweeds, and the confirmation of the presence of GA precursors in red seaweeds is needed to understand the evolutional diversity of GA biosynthesis in plants.…”
Section: Phytohormones In Red Seaweeds: Presence Of Particular Hormonmentioning
confidence: 99%
See 1 more Smart Citation
“…However, P. yezoensis and B. fuscopurpurea have no OPDA (Mori, Matsuura and Mikami, unpublished), which is consistent with the lack of JA in these Bangiophyceae. Moreover, in P. patens, despite the absence of bioactive GA 1 and GA 4 , the precursors ent-kaurene and ent-kaurenoic acid and also their metabolites other than GAs regulate red light-dependent cellular differentiation and blue light-dependent negative phototropism (Hayashi et al 2010, Miyazaki et al 2014, 2015. However, little is known so far about the presence of these molecules in red seaweeds, and the confirmation of the presence of GA precursors in red seaweeds is needed to understand the evolutional diversity of GA biosynthesis in plants.…”
Section: Phytohormones In Red Seaweeds: Presence Of Particular Hormonmentioning
confidence: 99%
“…Based on the most extensive studies of interactions between bacteria and marine green seaweeds to date (Joint et al 2007, Wichard 2015, the association of seaweeds with epiphytic bacteria is commonly thought to be essential for their normal growth, morphogenesis, and reproduction (Egan et al 2013, Singh and Reddy 2014, Wichard 2015, Liu et al 2017). In addition to exchanges of nutrient chemicals and morphological regulators (Egan et al 2013, Singh and Reddy 2014, Wichard 2015, bacterium-derived IAA is involved in bud formation in the Florideophyte Gracilaria dura (Singh et al 2011a). With regard to phytohormones, it was recently reported that diatoms receive IAA from their symbiotic bacteria, and these are required for efficient growth (Amin et al 2015).…”
Section: Are Phytohormones Synthesized By and Transferred From Symbiomentioning
confidence: 99%
“…Instead, the alga forms callus-like, slow growing structures with colourless protrusions from the exterior cell wall (Spoerner et al 2012, Wichard 2015. Early experiments of Provasoli (1958) have already pointed out that treatment of Ulva with antibiotics results in abnormal growth.…”
mentioning
confidence: 99%
“…Further experiments examined the role of isolated bacteria in activating developmental and growth promoting traits in Ulva and revealed species-specific interactions, as no combination of bacteria showed the complete recovery of the normal morphotypes (Provasoli and Pintner 1980, Marshall et al 2006, Spoerner et al 2012, Wichard 2015. Two bacterial isolates from non-axenic laboratory cultures of U. mutabilis were later found to induce the complete morphogenesis of U. mutabilis, forming a tripartite community (Spoerner et al 2012, Wichard 2015. The bacterial strains were originally described as Roseobacter sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation